2022
DOI: 10.21037/apm-22-1099
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the factors associating the willingness of Chinese community residents to receive COVID-19 vaccine

Abstract: Background: Amid the coronavirus disease of 2019 (COVID-19) pandemic, China's vaccination campaign is progressing in an orderly manner. In the process of vaccination, the vaccination rates in different parts of China are different, and the factors affecting people's vaccination are also different, which may be caused by some reasons affecting people's willingness to vaccinate or complex sociodemographic characteristics factors.We found that inconsistent findings on factors associated with willingness to get CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Multivariate regression results demonstrated that gender was an independent determinant of regular COVID-19 vaccine hesitancy with females more likely to be hesitant. Although gender was not identified as a significant predictor of hesitancy in existing studies on regular COVID-19 vaccination [ 5 , 16 , 17 ], our finding aligned with previous studies on basal or booster doses of vaccines [ 14 , 39 , 40 ]. Particular concerns from females on COVID-19 vaccines include pregnancy, breastfeeding, and the long-term effects that vaccines may have on offspring [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate regression results demonstrated that gender was an independent determinant of regular COVID-19 vaccine hesitancy with females more likely to be hesitant. Although gender was not identified as a significant predictor of hesitancy in existing studies on regular COVID-19 vaccination [ 5 , 16 , 17 ], our finding aligned with previous studies on basal or booster doses of vaccines [ 14 , 39 , 40 ]. Particular concerns from females on COVID-19 vaccines include pregnancy, breastfeeding, and the long-term effects that vaccines may have on offspring [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…A recently published meta-analysis described an association between people's gender, place of residence, sociodemographic characteristics and their willingness to be vaccinated against . This study showed that Chinese men are 1.48 times more likely to be vaccinated against COVID-19 than women are (17). No similar study specifically for COPD patients was found in the international and national literature, the uptake of the first booster vaccine COVID-19 among COPD patients in Hungary and its related factors have not been investigated yet.…”
Section: Introductionmentioning
confidence: 69%
“…16 [11][12][13][14][15][16][17][18][19][20][21] vs. 14 [10-19], P<0.001, modified Medical Research Council (mMRC) dyspnea scale: 2 [2-2] vs. 2 [1-2], P=0.01 and in the number of moderate exacerbations: 1 [0-1] vs. 0 [0-1], P=0.04. In addition, who did not take the third vaccination significantly more people were hospitalized for acute severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (16 vs. 0, P<0.001) and almost the same proportion (n=14) required pulmonary outpatient rehabilitation for post-COVID symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations